Diagnosis of Caroli’s Disease: a Rare Case Report (Bangladesh Medical Journal, 2024)
Caroli’s disease is a rare disease caused by Ductal Plate malformation. Patients may present with history of intermittent abdominal pain, pruritus and/ or symptoms of cholangitis. Cholangitis, liver cirrhosis, and cholangiocarcinoma arepotential complications. It is rarely diagnosed in childhood. A six (06) years old was presented with intermittent abdominal pain, fever, pruritus, and hepatomegaly at the Department of Paediatric Gastroenterology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh. After evaluating history, signs/ symptoms, physical examination, biochemical, ultrasonographic and endoscopic !ndings; this case was provisionally diagnosed as a compensated chronic liver disease with portal hypertension due to cause of cholestasis. Finally magnetic resonance cholangiopancreatography (MRCP) was done for further evaluation and the diagnostic !ndings of MRCP was suggestive of Caroli’s disease. After consultation the MRCP report with Pediatric Surgery Department of BSMMU the patient was advised for liver transplantation due to multifocal involvement of liver. Lastly patient was discharged with supportive management.Bangladesh Med J. 2022 Sept; 51(3): 43-46